Performance Evaluation of Delay and Jitter in Optical Fiber Networks for Real-Time Multimedia Applications - Ayu Mika Sherila; Melisa Mulyadi (Jurnal Elektro, 2025)
The increasing reliance on real-time services such as VoIP and video streaming underscores the critical role of fiber optic networks as high-capacity communication backbones. While optical fibers offer substantial bandwidth, this alone does not ensure optimal Quality of Experience (QoE); network delay and jitter remain prominent challenges that can disrupt audio clarity and video continuity. This paper presents a detailed analysis of delay and jitter phenomena within fiber optic systems, particularly emphasizing Passive Optical Network (PON) topologies. It explores the underlying causes of performance degradation from physical-layer limitations to architectural inefficiencies and critically assesses current mitigation techniques implemented at both the network level (e.g., Quality of Service mechanisms) and application level (e.g., jitter buffering strategies). The main contribution of this work is the introduction of a novel "Cross-Layer Performance Optimization Framework," which addresses the disconnect between static QoS enforcement and reactive application adaptations. By fostering dynamic interaction between the network and application layers, this framework aims to enable predictive control mechanisms that better safeguard user experience. Ultimately, this approach offers a pathway to more robust and efficient delivery of real-time services over next-generation optical access networks.